2018
DOI: 10.1016/j.humov.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Onward and upward: Optimizing motor performance

Abstract: In the OPTIMAL theory of motor learning (Wulf & Lewthwaite, 2016), three factors are postulated to facilitate motor performance and learning: Enhanced expectancies (EE) for performance, autonomy support (AS), and an external focus (EF) of attention. We examined whether EE, AS, and EF would have immediate performance benefits and whether implementing these factors consecutively would lead to incremental performance increases. Participants were assigned to the optimized or control groups and performed a maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 66 publications
4
33
0
3
Order By: Relevance
“…Promoting perceived competence is important for motivation, learning and performance (Wulf & Lewthwaite, 2016). Providing positive feedback during/after successful performance, while ignoring less successful performances generally increases perceived competence and benefits learning and motivation (Chua, Wulf, & Lewthwaite, 2018;Wulf & Lewthwaite, 2016;Wulf, Lewthwaite, Cardozo, & Chiviacowsky, 2018). Continuously informing a runner of errors is therefore not optimal to increase perceived competence and hence motivation (Colley et al, 2018) and also not for learning because the runner is only informed about what is wrong and not how to correct it (Jensen & Mueller, 2014).…”
Section: Theory and Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Promoting perceived competence is important for motivation, learning and performance (Wulf & Lewthwaite, 2016). Providing positive feedback during/after successful performance, while ignoring less successful performances generally increases perceived competence and benefits learning and motivation (Chua, Wulf, & Lewthwaite, 2018;Wulf & Lewthwaite, 2016;Wulf, Lewthwaite, Cardozo, & Chiviacowsky, 2018). Continuously informing a runner of errors is therefore not optimal to increase perceived competence and hence motivation (Colley et al, 2018) and also not for learning because the runner is only informed about what is wrong and not how to correct it (Jensen & Mueller, 2014).…”
Section: Theory and Evidencementioning
confidence: 99%
“…• Autonomy reflects the ability to exercise control and numerous studies have shown that an enhanced perceived autonomy improves learning. Being able to choose when feedback is received, for example, led to enhanced learning in several discrete skills (Chua et al, 2018;Wulf & Lewthwaite, 2016;Wulf et al, 2018). Anecdotal evidence shows that runners also like to select the type of data provided as feedback (Kuru, 2016) and like to be in control of the extent to which they receive feedback (Mueller et al, 2010).…”
Section: Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, OPTIMAL theory identifies three distinct and partially independent motivational (enhanced expectancies, autonomy support) and attentional (external focus) motor learning factors/principles (i.e., "pillars") theorized to leverage the capacity for CNS plasticity to achieve enhanced motor behavior through adaptive neuroplasticity [160]. Further, the pillars of OPTIMAL motor learning can be combined for more robust, additive effects [1,23,102,103,106,128,161], but a conceptual framework for application of OPTIMAL theory in the context of ACL injury management strategies in youth-inclusive of prevention, rehabilitation, and exercise performance more generally-has yet to be proposed. A better mechanistic understanding regarding the role of motor learning on the CNS may help practitioners 'buy-in' and implement such methods in practice.…”
Section: The Solution: Optimal Prep Strategies For Injury Resistant Mmentioning
confidence: 99%
“…Während jeder dieser einzelnen Faktoren an sich wichtig ist, zeigen die jüngsten Ergebnisse, dass sich deren Effekte aufaddieren [5]. Wenn alle drei Faktoren vorhanden sind, führt das zu den effektivsten Lernergebnissen [28].…”
Section: Zusammenfassung Und Schlussfolgerungenunclassified